2021
DOI: 10.18203/2349-2902.isj20214756
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of antiglide plate in vertical shear fractures of medial malleolus due to supination adduction injury around ankle: a prospective clinical study

Abstract: Background: Ankle fractures represent 10% of all fractures with an incidence of around 137/100000 population per year, making these the second most common lower limb fractures after hip fractures. Increasing age, obesity and alcohol abuse are the major causal factors for the fractures around the ankle joint. These are typically low energy injuries with the majority occurring due to simple falls or sport. The aim was to open reduction and internal fixation of these with an antiglide plate.Methods: The present p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Out of total 30 patients considered in study 20 (66.66%) were male and 10 (33.33%) were female. Similarly, Arora et al, 7 demonstrated that the 64% of their studied cases were in age group 41-50 years. The majority of them (84%) were males.…”
Section: Case (1)mentioning
confidence: 70%
“…Out of total 30 patients considered in study 20 (66.66%) were male and 10 (33.33%) were female. Similarly, Arora et al, 7 demonstrated that the 64% of their studied cases were in age group 41-50 years. The majority of them (84%) were males.…”
Section: Case (1)mentioning
confidence: 70%
“…However, few other pieces of literature work show contradicting results depicting antiglide plates to be better than neutralization plates. 3,4 However, various techniques are available for the fixation of Vertical shear fractures of the medial malleolus including antiglide plates, tension bands, cancellous screws, and cortical screws in various configurations. Clinically, to manage these fractures, two partially threaded parallel screws of 4.0mm are used.…”
Section: Introductionmentioning
confidence: 99%